Niveles de estrés por COVID 19 en mujeres gestantes en el municipio de Albania La Guajira (2023)
The main objective of this study was to determine the levels of stress due to COVID 19 in pregnant women who attended prenatal check-ups at the San Rafael Hospital in the municipality of Albania La Guajira. For this, a simple random probabilistic sample of 90 voluntary participants, attending the health entity, was taken. The COVID 19 Stress Scale translated and validated with the Colombian adult population by Pulido & Jiménez (2020) was applied. The study corresponded to the quantitative approach, being of a non-experimental design, descriptive scope and cross section. The main results show that the vast majority of the participants were of legal age and some adolescents over 15 years of age, it was possible to show that there is a low level of risk with a percentage of 1% and there was a high level of risk with a percentage of 78%, that is, more than 50% of the study participants were affected by high levels of stress before COVID - 19. On the other hand, the main stressor of the symptoms of stress level before COVID corresponds to the verification of compulsive behaviors, with 98% of the participants, in second place, the stressor damage with 49%. Likewise, in third and fourth place are the levels of posttraumatic stress with 47%, and the socioeconomic consequences with 41% of the affected participants and finally, xenophobic concerns and contamination before the virus affected a third of the participants.